Tata Kelola Bumdes Luberti Jaya Dalam Upaya Meningkatkan Pendapatan Desa Di Desa Lubuk Bendahara Timur Kecamatan Rokan IV Koto - Tampubolon, Merlin Dortua; Mayarni, Mayarni (Peneliti.net, 2023)
The Rokan IV Koto sub-district has a BUMDes with sound credibility called BUMDes Luberti Jaya and is located in Lubuk Bendahara Timur Village. Village income contributed by BUMDes Luberti Jaya is quite small considering the slow pace of development of each existing business unit. This study aims to identify the governance of BUMDes Luberti Jaya and look at the obstacles that have caused a slowdown in BUMDes Luberti Jaya. Mardiasmo's theory (2018) is used as a theory, namely, good governance with four indicators: transparency, accountability, responsibility and equity. Using qualitative research methods with a descriptive approach. This research shows that BUMDesa Luberti Jaya has not succeeded in increasing village income in Lubuk Bendahara Timur village. This is because BUMDesa Luberti Jaya cannot maximize village income to establish its own village. shows that leadership is a barrier to the implementation of Luberti Jaya's first BUMDes governance. And the second is talking about community participation, it can be seen that the community is not very interested in building BUMDes. Lastly, elements of society do not have the motivation to participate and are less active..